Initial ergonomics risk assessment (ERA) in the library conducted by ergonomics trained person (ETP) in evaluating potential ergonomic risk factors (ERFs). - Mohd Roshdi, Farrah Rina (International Journal of Accounting, Finance and Business, 2025)
The library environment encompasses a range of activities, including reading, computer usage, book shelving, and customer service responsibilities, all of which might provide ergonomic hazards. An Initial Ergonomics Risk Assessment (ERA) is conducted to identify and reduce these hazards in order to enhance user comfort, health, and productivity. The objective of the Initial Ergonomics Risk Assessment (ERA) in the library is to detect potential ergonomic hazards that could lead to musculoskeletal diseases (MSDs) among library staff and patrons. This assessment will concentrate on examining the selected physical arrangement and activities carried out in the library in order to suggest enhancements that improve ergonomics and decrease the likelihood of harm. Research technique is performing systematic inspections to visually observe the ongoing activities, capture images, and collect pertinent details regarding the existing procedures and utilized machinery. Conduct interviews and surveys with library personnel and patrons to gather their feedback on ergonomic issues and areas that want enhancement. The risks are then prioritized based on their impact. Create actionable suggestions to minimize identified hazards, such as modifying furniture, equipment, task protocols, and layout configurations. Prior to lifting heavy things, engage in a warm-up routine and perform stretching exercises to enhance muscle flexibility Fand lower the chances of strains and sprains. If the above recommendation is improved, no requirement for the Advanced ERA.